Perlindungan Hukum terhadap Anak sebagai Pelaku Pelecehan Seksual Menurut UU No. 35 Tahun 2014 - Desi Nellyda; I Nyoman Sujana; Luh Putu Suryani (Warmadewa Press, 2020)
This thesis is titled â€œLegal Protection Toward Child As Offenders Of Sexual Harassment, According Indonesian Law No. 35 Year 2014â€. The writing uses normative research method, by using statue approach and conceptual approach. The problem formulations are: (1) The shape of legal protection toward child as offenders of sexual harassment ; (2) The imposition of criminal sanctions against ch ild who commit sexual abuse. By reviewing the law research done by using the proposed studi above, it can be concluded that the first problem formulation related to the shape of legal protection toward child as offenders of sexual harassment according Indonesian Law No. 35 Year 2014 about the change of the Law No. 23 Year 2002 about Child Protection, the child has a right to accompanied by advocate during the process of investigation. Meanwhile, the second formulation will discuss the imposition of criminal sanctions against child who commit sexual abuse which have been regulated at the Article 82 Indonesian Law No. 35 Year 2014 about the change of the Law No. 23 Year 2002 about Child Protection. Depend on the Article 82 the offenders can be sentenced to prison the shortest 5 (five) years and the longest 15 (fifteen) years and a maximum fine of Rp. 5.000.000.000,00 (five billion dollars).